The Correlation of Parenting Sytle with Children Social Emotional Development in Kindergarten School At Xaverius 1 Jambi - Pangaribuan, Tumewa (Indonesian Journal of Early Childhood Education Studies, 2017)
Parenting syle is the way for parents interact with their children. Some styles that can be done for applying in parenting sytle, they are; authoritarian, permissive and authoritative. These parenting sytles should be dealt with family needs. Later, it will help to impact to child development. Some children raised in dramatically different environments can later grow up to have remarkably similar personalities. Conversely, children who share a home and are raised in the same environment can grow up to have astonishingly different personalities. The findings of this study indicated that parenting styles influence the formation of children behavior and personality